An inverse problem for the heat equation in an unbounded guide. (December 2016) - Cardoulis, Laure; Cristofol, Michel
Abstract: In this paper we prove a stability result for the reconstruction of the potential q associated with the operator ∂ t − Δ + q in an infinite guide using a finite number of localized observations.